Production of alpha humulene and zerumbone in adventitious root cultures of Zingiber zerumbet (L.) smith through synergistic effect of elicitors and plant growth regulators / Nurul Huda Alwakil - Nurul Huda , Alwakil (2021)
Plant secondary metabolites are gaining huge interest from their phytomedical potential viz. antimicrobial, anticancer, anti-inflammatory, drug and pesticides. There are many active researches being carried out to isolate and commercialize these valuable bio-products. Plant cell culture is a feasible alternative route to produce the bioactive compounds as its offers good quality materials less affected by uncertainties in environmental, ecological or climatic conditions. Zingiber zerumbet Smith widely known as shampoo ginger or common to Malay as ‘Lempoyang’ is a small perennial medicinal herb plant belonging to the Zingiberaceae family. Zerumbone presents dominantly in the rhizome of Zingiber zerumbet with α-humulene as its intermediate, and exhibits important phytomedicinal properties such as anticancer, antimicrobial, anti-inflammatory, antinociceptive, chemopreventive and antioxidant. Efficient production of zerumbone through the establishment of adventitious root culture has been investigated previously. However, the production of α-humulene and the synergistic effects of elicitors on the production of α-humulene and zerumbone in vitro are yet to be investigated. The combination of auxin-auxin and auxin-cytokinin causes a significant decrease in adventitious root growth at high IBA and BAP concentrations. The highest specific growth rate for root biomass production is obtained on media supplemented with 5 mg L-1 IBA and 1 mg L-1 NAA with maximum fresh weight of 6.90 ± 0.08 g and dry weight of 2.10 ± 0.01 g was not significant with 3 mg L-1 BAP and 1 mg L-1 NAA. Meanwhile, maximum productions of α-humulene (3759 ± 798 μg/g) and zerumbone (3440 ± 168 μg/g) are observed in the media containing 3 mg L-1 BAP and 1 mg L-1 NAA under 16:08 photoperiod along with abundant root biomass (1.90 ± 0.05 g DW). Elicitation studies shows that root growth and compounds production are negatively correlated events, which a significance decline in biomass growth is observed with the increase in elicitor concentration. The yields of zerumbone and α-humulene at 43 mg/g DW and 15.8 mg/g DW, respectively are obtained at low concentration range of elicitors i.e. 400μM to 600μM methyl jasmonate and salicyclic acid and represent better production compared to control. In conclusion, synergistic effects from application of elicitor combination to induce excess secondary metabolites in plant culture could be a practical route for larger scale production.